The Tail of Two Countries: Minimum Wages and Employment in France and the United States - John M. Abowd; Francis Kramarz; David N. Margolis; Thomas Philippon (Institute for the Study of Labor (IZA), 2000)
We use longitudinal individual wage and employment data in France and the United States to investigate the effect of changes in the real minimum wage rate on an individual?s employment status. We focus on workers employed at wages close enough to the minimum in a reference year as to be illegal in an adjacent comparison year as a result of movements in the real minimum wage. We find that movements in the American real minimum wage are associated with no employment effects, whereas movements in the cost of French minimum wage workers are associated with very strong negative employment effects. Our analysis is based upon identifying the direct effect of the change in the real minimum wage rate on exits from (entry into) employment when the real minimum wage rate increases (respectively, decreases) and identifying the heterogeneity in the behavior of our treatment and control groups using a pseudoexperimental contrast. We relate the difference-in-difference estimator directly to demand and supply elasticities for the two groups.
Keywords: J31; J23; 330; Minimum wage; international comparisons; labor demand; labor costs; Mindestlohn; Arbeitskosten; Arbeitsnachfrage; Beschäftigungseffekt; Arbeitslosigkeit; Vergleich; Schätzung; USA; Frankreich